PENGARUH LATIHAN MEDICINE BALL ROTATIONAL SIDE THROW TERHADAP KEMAMPUAN LEMPAR CAKRAM MAHASISWA PENJASKESREK - Linda Susila; Sandi Achmat Pratama; Agus Setiawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
The main problem in this study is the low ability of students in throwing discus. This study aims to determine the effect of the medicine ball rotational side throw training method on improving the discus throwing ability of students in the Physical Education, Health, and Recreation study program at STKIP Yapis Dompu. The research method used an experiment with a one-group pretest-posttest design. The sample consisted of 30 male students selected using a purposive sampling technique. Data were analyzed using a paired sample t-test. The results showed that the calculated t-value of 55.24 was greater than the t-table of 2.045 at a significance level of 0.05, so there was a significant effect of medicine ball rotational side throw training on discus throwing ability. Conclusion: This training method can be used as an alternative training program to improve rotational strength, arm power, and discus throwing ability in athletics.